IMPLANTACIÓN DE UN SISTEMA CONTABLE A DISTRIBUCIONES "POVEDA" DE LA CIUDAD DE LORETO, PROVINCIA DE ORELLANA; PERIODO JULIO-SEPTIEMBRE DEL 2016 - Parreño Galora, Cledia Edelmira (2018)
The present research work was carried out with the purpose of providing an adequate and efficient Accounting System to know with certainty what the economic situation of the company is, likewise it was elaborated in consideration of the Regulation of Academic Regime of the National University of Loja, prior to choosing the degree in Accounting and Auditing. The objectives set were fulfilled in full, since the information was collected from different bibliographic sources, then the Plan and Accounts Manual was made according to the needs and characteristics of the company under study, the Initial Inventory, in which the Assets and Liabilities were defined, the same that allowed knowing the Equity that the distributor has, then proceeded to record in the Daily Book the opening entry and the other transactions raised in the business, continued with the Majorization, Worksheet and ended with the Financial Statements such as: the Income Statement, the Balance Sheet and the Cash Flow Statement. Once the accounting process was applied, it was found that the business of Mr. Alex Poveda Noboa obtained a profit in the accounting period during the established period. Finally, conclusions and recommendations are presented focused on providing guidance to the owner in accounting aspects, recommending the implementation of accounting, since it consists of a financial structure that allows you to obtain timely and accurate information to make the best decisions directed to progress and growth your business